PENCANTUMAN KLAUSUL ARBITRASE DAN AKIBAT HUKUMNYA PADA KONTRAK ANTARA DEVELOPER DAN KONSUMEN - MHD. ARIF SYAHPUTRA PANJAITAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. T. Keizerina Devi A3. Mahmul Siregar Some conclusions; namely, the inclusion of comprehensive arbitration clauses all the important elements stated in the Law No.30/1999 about arbitration and alternatives to settle conflicts were cautiously and carefully made. There were at least nine elements which should be approved by the parties; namely, the forum to settle the conflicts, the standard of arbitration clause, the location of arbitration, the choice of forum implemented, the composition of arbitration board, the language of arbitration process, the final binding verdict, the implementation of the verdict on arbitration, and cost of arbitration. The implementation of arbitration clauses between the developer and consumer was the implementation made in written by the developer and consumer before or after the conflicts occur. The implementation of arbitration clauses was based on the arbitration clauses arranged completely, clearly, and cautiously.Keywords: Arbitration Clause, Legal Consequence, Consumer, Developer.